Concentration-dependent apparent partition coefficients of ionic liquids possessing ethyl-and bi-sulphate anions - Jain, Preeti; Kumar, Anil (Physical Chemistry Chemical Physics, 2016)
This study deals with the concentration dependent apparent partition coefficients log P of the ethyl and bisulfate-based ionic liquids. It is observed that the bisulfate-based ionic liquids show different behaviour with respect to concentration as compared to ethyl sulphate-based ionic liquids. It is significant and useful analysis for the further implementation of alkyl sulfate based ionic liquids as solvents in extraction processes. The log P values of the ethyl sulphate-based ionic liquids were noted to vary linearly with the concentration of the ionic liquid, whereas a flip-flop trend with the concentration for the log P values of the bisulphate-based ionic liquids was observed due to the difference in hydrogen bond accepting basicity and possibility of aggregate formation of these anions. The pi-pi interactions between the imidazolium and pyridinium rings were seen to affect the log P values. The alkyl chain length of anions was also observed to influence the log P values. The hydrophobicity of ionic liquid changes with the alkyl chain in the anion in the order; [HSO4](-) < [EtSO4](-) < [BuSO4](-).

Isothermal titration calorimetric study of the ionic liquid solutions in alcohols in extreme dilutions: an investigation of ion-solvent interactions - Rai, Gitanjali; Jain, Preeti; Kumar, Anil (Journal of Solution Chemistry, 2016)
In this work an effort has been made to show the effect of an alcohol-rich environment on imidazolium-based ionic liquids at 298.15 K using an isothermal titration calorimeter. It is divulged from this study that the thermal behavior expressed in terms of excess partial molar enthalpy, \( H_{\text{IL}}^{\text{E}} \), of ionic liquids in various linear alcohols is governed by the increasing hydrophobicity of the residual alkyl group attached to the cation of an ionic liquid and to the alcohol molecules. An interesting observation about the systems consisting of ethylated residuals on both the cations of the ionic liquid and the alcohol molecules is that these systems do not follow the trend exhibited by other ionic liquid–alcohol systems. Interesting information on ionic interactions is obtained by using a simple methodology that gives the enthalpic interaction parameter \( H_{{I{\text{L - IL}}}}^{\text{E}} \).
Keywords: Ionic liquidsAlcoholsExcess enthalpyIsothermal titration calorimeter

Comparable ionicity of the solutions of aprotic and protic ionic liquids by anion substitution - Jain, Preeti; Kumar, Anil (Journal of Solution Chemistry, 2017)
Temperature dependent molar conductances and fluidities of bisulfate and ethyl sulfate anion-based ionic liquids were measured. The extent of dissociation of the ionic liquids was estimated from the Walden plot in term of ionicity. The ionicity mainly depends on the magnitude of Coulombic forces, altered by the anion’s Lewis basicity. Aqueous solutions of aprotic ionic liquids, in general, possesses ionicity in the range of ≈70–99%. This article reveals that the substitution of the anion by bisulfate and ethylsulfate reduces the ionicity of aqueous solution of these ionic liquids to the range of 10–37%. This is very close to that exhibited by some of the protic ionic liquids and phosphonium based ionic liquids with sweetner anions. The concentration dependent molar conductance of these ionic liquids has been fitted to Mahiuddin and Ismail’s equation. To our surprise, the molar conductances of bisulfate-based aprotic ionic liquids are remarkably high, even though these ionic liquids possess lower ionicity.

Probing the solute-solvent interactions in the binary mixtures of ionic liquids with water and alcohols by conductance, viscosity and IR spectroscopy - Jain, Preeti; Kumar, Anil (Journal of Molecular Liquids, 2017)
The molar conductance and viscosities of the bisulfate ([HSO4](-)) and ethylsulfate ([EtSO4](-))-based imidazolium ionic liquids in various molecular solvents have been measured at 298.15 K as a function of concentration of ionic liquids (1 x 10(-4) to 0.1 mol L-1). It is shown that the anions have considerable effect on the molar conductance and association constant of the [HSO4](-) and [EtSO4](-)-based imidazolium ionic liquids. Higher molar conductance of the [HSO4](-)-based imidazolium ionic liquids in polar protic solvents (water and methanol) is noted as compared to the [EtSO4](-)-based imidazolium ionic liquids, though the [HSO4](-)-based imidazolium ionic liquids possess higher association constant in water than in methanol. The intermolecular interactions in the pure and binary mixture of [HSO4](-) and [EtSO4](-)-based imidazolium ionic liquids have been investigated by IR spectroscopy. The C-2-H stretching vibration frequency of the imidazolium ring reveals the H-bonding between cations and anions of pure ionic liquids and their solutions. The transport properties (limiting molar conductance, transport number, ionic mobility and diffusion coefficient) of cations and anions correlate well with the hydrodynamic radius in their aqueous solutions. The study shows that the energy barrier for charge transfer is minimal as compared to the fluidity of the aqueous solution of the studied ionic liquids obtained from the Arrhenius equation. (C) 2017 Elsevier B.V. All rights reserved.

Enthalpic interactions in aqueous strong electrolytes upon addition of ionic liquids - Jain, Preeti; Kumar, Anil (Physical Chemistry Chemical Physics, 2018)
The present study deals with the inter-ionic interactions between strong electrolytes and ionic liquids based on the thermodynamic properties such as excess partial molar enthalpy, H-IL(E), relative apparent molar enthalpy, phi(L), and the enthalpic interaction parameters. The thermodynamic properties of the systems are the key indicators to understand the interionic interactions. We have conducted a systematic investigation of the enthalpic behavior of aqueous solution of salts and ionic liquids and their mixtures. The present study also emphasizes how the H-IL(E) values for the mixture of aqueous solution of ionic liquids and salts deviate from linearity as compared to those of the constituent aqueous ionic liquid or salt. This deviation from linearity for the H-IL(E) values has been discussed here.

Structural elucidation of the binary mixtures of [emim][bf4] and [bmim][bf4] in ethyl-substituted solvents by isothermal titration calorimeter. - Jain, Preeti (ChemistrySelect, 2018)
In order to address the issue whether both ionic liquids and solvents influence the enthalpy of their solutions, highly accurate excess partial molar enthalpy, urn:x-wiley:23656549:media:slct201800976:slct201800976-math-0001 values have been measured using Isothermal Titration Calorimeter (ITC). Therefore, thermodynamic behavior has been observed in the mixtures containing ionic liquids. It essentially depends on the molecular structure of the constituents of the mixture. The hydrogen bonding between ionic liquids and ethyl‐substituted solvents (2‐ethoxyethanol, ethylene glycol, diethylamine, ethyl acetate and N,N‐ diethylacetamide) may lead to strong ion‐solvent interactions. In the present study, an effort has been made to quantify various interactions between ionic liquid and solvent, based on the urn:x-wiley:23656549:media:slct201800976:slct201800976-math-0002 values. Linear solvation free relation shows dependence of limiting excess partial molar enthalpies, urn:x-wiley:23656549:media:slct201800976:slct201800976-math-0003 upon the solvent properties. Structural orientation of solvent molecules and ionic liquids also described by the urn:x-wiley:23656549:media:slct201800976:slct201800976-math-0004 values. The ion‐ion, ion‐solvent interactions have also been investigated in terms of the enthalpic interaction parameters, urn:x-wiley:23656549:media:slct201800976:slct201800976-math-0005 and relative apparent molar enthalpy, φL of ionic liquid‐ethyl‐substituted solvent systems.

Operando X-ray absorption spectroscopy study of the Fischer-Tropsch reaction with a Co catalyst - Nayak, Chandrani; Jain, Preeti; Vinod, C. P.; Jha, S. N.; Bhattacharyya, D. (Journal of Synchrotron Radiation, 2019)
This article describes the setting up of a facility on the energy-scanning EXAFS beamline (BL-09) at RRCAT, Indore, India, for operando studies of structure-activity correlation during a catalytic reaction. The setup was tested by operando X-ray absorption spectroscopy (XAS) studies performed on a Co-based catalyst during the Fischer-Tropsch reaction to obtain information regarding structural changes in the catalyst during the reaction. Simultaneous gas chromatography (GC) measurements during the reaction facilitate monitoring of the product gases, which in turn gives information regarding the activity of the catalyst. The combination of XAS and GC techniques was used to correlate the structural changes with the activity of the catalyst at different reaction temperatures. The oxide catalyst was reduced to the metallic phase by heating at 400 degrees C for 5h under H-2 at ambient pressure and subsequently the catalytic reaction was studied at four different temperatures of 240, 260, 280 and 320 degrees C. The catalyst was studied for 10h at 320 degrees C and an attempt has been made to understand the process of its deactivation from the XANES and EXAFS results.
Keywords: catalysis; EXAFS; Fischer-Tropsch reaction; in situ studies; structure-activity correlation; XANES

Water-assisted stability of carbene: cyclic voltammetric investigation of 1-ethyl-3-methylimidazolium ethylsulfate ionic liquid - Jain, Preeti; Chaudhari, Vijay R.; Kumar, Anil (Physical Chemistry Chemical Physics, 2019)
In this work, we report electrochemical studies on imidazolium-based ionic liquids with an objective to explore the possibility of carbene formation in their dilute aqueous solutions. Conventionally, water plays a detrimental role during investigations involving ionic liquids, and this role has been investigated via electrochemical studies in aqueous ionic liquid solutions. There are varying opinions regarding the influence of water on the physicochemical behaviour of ionic liquids that require an in-depth understanding. To eludicate the role of water, we attempted to evaluate the electrochemical performance of ionic liquids in water as a solvent, and the influence of water on ionic liquids was explored through feasibility and stability studies on carbene formed in an aqueous imidazolium-based ionic liquid solution. The electrochemical investigation of an aqueous solution of 1-ethyl-3-methylimidazolium ethylsulfate ([EMIM][EtSO4]) revealed a redox couple. Detailed investigations suggest that reduction of the imidazolium cation occurs at the C2 position, with subsequent formation of carbene. Furthermore, an anodic peak was found to be associated with the oxidation of carbene. The coulometric process associated with the anodic peaks indicated that the two-electron oxidation of carbene occurred. The stability of carbene in water was evaluated through the use of different protic and aprotic solvents. The hydrogen bond-forming ability of carbene with water seems to be responsible for its improved stability in water.

Role of exposed crystal facets in the atmospheric pressure CO hydrogenation on Co3O4 - Jain, Preeti; Gupta, Sharad; Vinod, C. P. (Nano-Structures & Nano-Objects, 2020)
Co3O4 nanostructures with different exposed planes are studied for atmospheric pressure CO hydrogenation. Existence of different facets is characterized by HR-TEM and found Co3O4 - NSP (nanospheres) expose (112) facet, NB (nanobelts) exhibit (110) plane and (100) is the dominant surface facet in NC (nanocubes). Different catalytic activity is demonstrated by the specific facet of Co3O4 catalysts. CO hydrogenation is facet dependent and the catalytic activity follows the order of Co3O4-NB > Co3O4-NC > Co3O4-NSP.

Morphology-dependent catalysis by Co3O4 nanostructures in atmospheric pressure carbon dioxide hydrogenation - Gupta, Sharad; Jain, Preeti; Jagadeesan, Dinesh; Vinod, C. P. (Journal of Physical Chemistry C, 2023)
In this work, three Co3O4 nanostructureswith different morphologies (cubes, rods, and sheets) were synthesizedusing a hydrothermal method and tested for the CO2 hydrogenationreaction. The physicochemical properties of the structured Co3O4 were well characterized by X-ray diffraction(XRD), Raman spectroscopy, field-emission scanning electron microscopy(FESEM), transmission electron microscopy (TEM), high-resolution transmissionelectron microscopy (HRTEM), hydrogen temperature-programmed reduction(H-2-TPR), and X-ray photoelectron spectroscopy (XPS) techniques.Based on the characterization, cube, rod, and sheet Co3O4 nanostructures were found to expose the (100), (110),and (112) planes, respectively. The effect of cobalt oxide morphologieswith different exposed surfaces on the activity and selectivity towardCO(2) hydrogenation reaction in a plug-flow reactor operatedbetween 200 and 400 & DEG;C under atmospheric pressure conditionswas explored. The results establish a correlation of the catalyticactivity with morphological structures in the order rods > sheets> cubes. H-2-TPR and XPS studies demonstrated that thehighreducibility of Co3O4 rod makes it an excellentcatalyst for CO2 hydrogenation.